Patient Safety Escape Room: A Graduate Medical Education Simulation for Event Reporting - Gretchen Diemer (Association of American Medical Colleges, 2019)
Introduction Although residents are on the front lines of patient care, they enter few formal patient safety reports on the adverse events and near misses they witness. Demonstrating the rationale and mechanics of reporting may improve this. Methods We designed and implemented an escape room patient safety simulation to incorporate active learning, gamification, and adult learning theory into intern patient safety onboarding. Interns from all sponsoring institution programs participated, identifying, mitigating, and reporting a range of patient safety hazards. Props and faculty time were the major resources required. Results One hundred twenty interns participated in this simulation in June 2018. Forty-one percent reported previous training on reporting errors, and only 5% had previously entered an event report. Average confidence in ability to identify patient safety hazards improved after the simulation from 6.35 to 8.00 on a 10-point rating scale. The simulation was rated as relevant or highly relevant to practice by 96% of interns. Discussion Several factors contribute to a low error-reporting rate among house staff. We developed a simulation modeled on popular escape room activities to increase awareness of safety hazards and ensure familiarity with the actual online reporting system our interns will use in the clinical environment.